Hospimeal: Website Based Nutrition Care Process Digitalization - Restuti, Arisanty Nursetia; Jannah, Miftahul; Iqbal, Muhammad (International Journal of Healthcare and Information Technology, 2024)
The nutrition Care Process (NCP) is a systematic approach or standard to provide comprehensive nutritional care for patients or clients. NCP consists of 4 interrelated steps, namely nutrition assessment, nutrition diagnosis, nutrition intervention, nutrition monitoring and nutrition evaluation. Implementation of NCP in many health services facilities face some barriers because of using manual NCP, such as human error, time-consuming, and incomplete documentation. Digitalization of NCP has proven to be beneficial in terms of efficiency of time and provision of electronic data to improve patient services. This study aimed to develop Hospimeal as a website-based Nutrition Care Process (NCP). The development of the web-based NCP application carried out in this study used the waterfall method. The stages of the waterfall method are need analysis, study of literature and data retrieval, system requirements, system planning, system implementation and testing, digitalization of NCP management in website. Digitalization of Standardized Nutrition Care Process (NCP) management can be developed in the form of a website called Hospimeal. This website provides nutritional care to patients/clients starting from nutrition assessment, nutrition diagnosis, nutrition intervention, nutrition monitoring, and nutrition evaluation. The Hospimeal website can be operated by the relevant nutritionist/dietitian. At the beginning of the display there is a Login menu which can be used by nutrition-ists/dietitians to enter the website